Headache and celiac disease or gluten sensitivity – a review - Melhado, Eliana Meire; Cardoso, Ana Carolina Botelho; Ribeiro, Stella Regina Mastrangi Ignácio; Frachia, Mariana de Lima; Castro, Thaís Figueiredo de (Headache Medicine, 2013)
The aim of this study is to do a review of the relationship of celiac disease (CD) or gluten sensitivity (GS) with headache.The authors conclude that there is a connection between headaches and gluten intolerance.